2008
DOI: 10.1021/jp8058068
|View full text |Cite
|
Sign up to set email alerts
|

Excited-State Intramolecular Proton Transfer Distinguishes Microenvironments in Single- And Double-Stranded DNA

Abstract: Herein, the efficient interaction of an environment-sensitive fluorophore that undergoes excited-state intramolecular proton transfer (ESIPT) with DNA has been realized by conjugation of a 3-hydroxychromone (3HC) with polycationic spermine. On binding to a double-stranded DNA (dsDNA), the ratio of the two emission bands of the 3HC conjugates changes up to 16-fold, so that emission of the ESIPT product increases dramatically. This suggests an efficient screening of the 3HC fluorophore from the water molecules i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
63
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 89 publications
(66 citation statements)
references
References 42 publications
3
63
0
Order By: Relevance
“…Photoinduced electron transfer and proton transfer are important fundamental processes for many biochemical reactions and find numerous applications in scientific field [1][2][3][4][5][6][7][8][9][10][11][12][13]. Amongst all the photoinduced processes, excited state proton transfer are of special interest.…”
Section: Introductionmentioning
confidence: 99%
“…Photoinduced electron transfer and proton transfer are important fundamental processes for many biochemical reactions and find numerous applications in scientific field [1][2][3][4][5][6][7][8][9][10][11][12][13]. Amongst all the photoinduced processes, excited state proton transfer are of special interest.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to such important applications, organic dyes undergoing ESIPT continue to receive wide attention from the experimental and theoretical aspects [1,[22][23][24][25][26][27][28][29][30][31][32][33][34]. Recently, Sakai et al reported the synthesis and comprehensive optical properties of a novel ESIPT fluorophore bearing the imidazole (Im) and benzothiazole (BT) moieties, 2-(1,3-benzothiazol-2-yl)-4-methoxy-6-(1,4,5-triphenyl-1H-imidazol-2-yl)phenol (BTImP) [1].…”
Section: Introductionmentioning
confidence: 99%
“…Ever since the seminal experimental observation of the excited-state intramolecular proton transfer (ESIPT) reaction of methyl salicylate (MS) by Weller et al in the middle of the last century [1], the phenomenon of photoinduced proton transfer process has attracted countless works in many fields of chemistry and molecular biology [2][3][4][5][6][7][8][9][10][11][12][13][14][15]. A very fascinating feature of molecules undergoing ESIPT is the presence of a strong intramolecular hydrogen bond, in which the acidity and basicity relations can be controllable by photoexcitation.…”
Section: Introductionmentioning
confidence: 99%